What's next for the Renewable Energy Target – resolving Australia's integration of energy and climate change policy?. (1st November 2021) - Nelson, Tim; Nolan, Tahlia; Gilmore, Joel
Abstract : Australian climate change policy and its integration with Australia's electricity markets have been fraught for at least two decades. The only enduring policy has been the Commonwealth Renewable Energy Target (RET). Despite the relative success of the RET in driving investment and reducing emissions, state governments have now pivoted towards contracts‐for‐difference (Cfds). In this article, we outline the issues associated with policy discontinuity and the large‐scale RET and review its effectiveness as an emissions reduction tool and driver of electricity sector abatement. We find that the RET has been relatively successful across the key criteria of cost and emissions reductions and is a better policy instrument than contracts‐for‐difference, which are increasingly being adopted by state governments. Building on the work of Nelson et al. (2020), we propose a new approach, which would allow for continued use of Cfds but utilising the RET's policy architecture.